2020
DOI: 10.37268/mjphm/vol.20/no.special1/art.697
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ergonomic Risk Factors Among Male Workers in a Medical Manufacturing Company in Northern Malaysia

Abstract: The medical manufacturing industry is currently one of the sectors with great potential growth in Malaysia, which offers numerous job opportunities to local and foreign workers. The growing proportion of workers in this industry means that a large number of workers are potentially exposed to ergonomic risk factors at the workplace, which may consequently affect their health. Thus, this study was carried out is to investigate the ergonomic risk factors and the prevalence of musculoskeletal disorders among male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…This study is in line with research studies that show that ergonomic risk factors have a significant relationship with back pain (Kee & Seo, 2007). Athirah and Nurul's (2020) study showed that the highest prevalence of musculoskeletal disorders among male workers in medical manufacturing companies was in the lower back (83.17%), upper back (4.38%), right shoulder (3.49%), and left shoulder (3.49%) . Next, the results of the study show that the dimension of awkward posture also has a significant and positive relationship with job stress among workers in the manufacturing sector (r = 0.213, k < 0.01).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This study is in line with research studies that show that ergonomic risk factors have a significant relationship with back pain (Kee & Seo, 2007). Athirah and Nurul's (2020) study showed that the highest prevalence of musculoskeletal disorders among male workers in medical manufacturing companies was in the lower back (83.17%), upper back (4.38%), right shoulder (3.49%), and left shoulder (3.49%) . Next, the results of the study show that the dimension of awkward posture also has a significant and positive relationship with job stress among workers in the manufacturing sector (r = 0.213, k < 0.01).…”
Section: Resultssupporting
confidence: 91%
“…While the results of the study show that the dimension of awkward posture also has a significant and positive relationship with occupational accidents among workers in the manufacturing sector (r = 0.358, k < 0.01). Athirah and Nurul's (2020) study also stated that 87.5 and 62.5% of participants were at high risk of injury and the risk of contributing to an accident based on the distance of their hands from the lower back and the grip of loads during duty.…”
Section: Resultsmentioning
confidence: 94%
“…Karimi et al (2020) did a special study in a milk factory, showing that starting ergonomic steps and manager decisions together made better ways of working and less muscle soreness. In making things, farming, health help, and building work areas, moving things many times don't think of ergonomics, causing MSDs (Susihono et al, 2018;Yusof & Shalahim, 2020;Marak et al, 2020;Qureshi et al, 2019;Curbano, 2018). Yusof & Shalahim (2020) saw that workers making things felt a lot of lower back MSDs, with lifting heavy things being a big danger.…”
Section: Addressing Musculoskeletal Discomfort In Materials Handling:...mentioning
confidence: 99%
“…The growing proportion of workers in manufacturing industry means that many workers are potentially exposed to ergonomic risk factors at the workplace, which may consequently affect their health. The authors suggested a guideline to implement interventional ergonomics programmes at the workplace and improve the musculoskeletal health of workers in the manufacturing industry in Malaysia (4). Ergonomics has gained attention and take into consideration by the workers in the different fields of works recently.…”
Section: Introductionmentioning
confidence: 99%